2018
DOI: 10.3390/colloids2010011
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and Hydration of Amphiphilic Hyperbranched Arabinogalactan-Protein from Plant Exudate: A Volumetric Perspective

Abstract: Plant Acacia gum exudates are composed by glycosylated hydroxyproline-rich proteins, which have a high proportion of heavily branched neutral and charged sugars in the polysaccharide moiety. These hyperbranched arabinogalactan-proteins (AGP) display a complexity arising from its composition, architecture, and conformation, but also from its polydispersity and capacity to form supramolecular assemblies. Flexibility and hydration partly determined colloidal and interfacial properties of AGPs. In the present arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 128 publications
(268 reference statements)
2
24
0
Order By: Relevance
“…This result is in agreement with the more compact conformation of gum with the increase of the salt concentration, as previously observed using QCM-D. The effect of the salt concentration was previously observed with a decrease of the macromolecule hydration through partial shielding of the charges of the gum in solution [7].…”
Section: Influence Of Salt Concentrationsupporting
confidence: 92%
See 4 more Smart Citations
“…This result is in agreement with the more compact conformation of gum with the increase of the salt concentration, as previously observed using QCM-D. The effect of the salt concentration was previously observed with a decrease of the macromolecule hydration through partial shielding of the charges of the gum in solution [7].…”
Section: Influence Of Salt Concentrationsupporting
confidence: 92%
“…1 I bu f f er = C tot * 10 pH−pKa 1+10 pH−pKa with C tot = 0.01 M and pK a = 4.75; 2 κ −1 = 0.304/I 1/2 From the QCM-D results, it was observed that A. seyal films are less stable and display a more compact and less viscoelastic behavior than A. senegal films regardless of the experimental conditions. This behavior may be related to the differences in the flexibility of each gum in solution [6,7], and the present study confirms that the A. senegal film has a more flexible and deformable structure than the more rigid A. seyal film. A. seyal films have close similarities to locust bean gum (LBG) films [41].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations